EFUSI PLEURA DEXTRA EC. TB PARU: LAPORAN KASUS - Fahmi Nofriandi; Astri Hindarti; Puan Sadila Islami (Jurnal Ilmiah Fisioterapi, 2023)
Pleural effusion is the accumulation of fluid in the pleural cavity due to transudation or excessive exudation from the pleural surface. In western countries, pleural effusion is mainly caused by congestive heart failure, cirrhosis of the liver, malignancy, and bacterial pneumonia, while in developing countries, such as Indonesia, it is commonly caused by tuberculosis infection. Good management is needed in tackling this pleural effusion, namely removing the fluid immediately and treating the cause so that the results will be satisfactory. This case reports a male twenty seven years complaining of shortness of breath since 1 week ago. Patients also complain of coughing, sweating at night, decreased body weight and fever. On physical examination of the thorax, right chest movement lags when breathing, palpation of tactile fremitus of the right lung is weak, dull percussion of the right lung is at ICS VII-X and vesicular auscultation is weakened at ICS VII-X right lung and crackles are found in both lung fields. Chest X-ray examination showed right pleural effusion. So that the diagnosis of pleural effusion dextra ec. pulmonary TB. The patient was managed with pleural puncture and OAT treatment